Comparison between the WNBA and WEL: differences and key performance indicators in top women basketball leagues - Jorge Lorenzo Calvo; Rafael Manuel Navarro Barragán; Carlos Serrano Luengo; Guillermo Muñoz Andradas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: This study focused on comparing performance between the WNBA and the Euroleague Women, identifying key variables to optimize key strategies in women's basketball.